(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Introduzione - 2. Primo Movimento: Il minore nel contesto familiare e nel gruppo religioso - 3. Secondo Movimento: Il ruolo del giudice, tra autodeterminazione in materia sanitaria e best interests of the child - 4. Terzo Movimento: Conclusioni. L’evoluzione del minore in una società plurale. The Children Act: Finding the best interests of the child between family, religious community and the court ABSTRACT: Connections that bring together law and literature unceasingly prove to be very meaningful. Ian McEwan’s novel, The Children Act, offers an intriguing example of law in literature, cannily managing the complex theme of religion and justice. A young Jehovah’s Witness affected by a severe disease refuses to have his life saved by a blood transfusion. The Family Court finds in favour of the medical treatment against the child and his family’s convictions but the ruling triggers an unpredictable chain of events culminating in a tragic epilogue. Similarities between the novel and real law cases about refusals of medical treatments on religious grounds are traced throughout the article, which aims at analysing the controversial relations among the subjects and interests involved when dealing with a child medical consent and conscientious objections, mainly the duties of the family, the rights of the child and the responsibilities of the state. Concluding remarks will highlight that, in order for the child to express an autonomous and informed consent, a thorough and critical education is needed, provided through a pluralistic learning environment and an inclusive social framework, as international bodies - like the UN Committee on the Rights of the Child - clearly suggest.